AKSESIBILITAS ANAK MENGIKUTI PENDIDIKAN ANAK USIA DINI DI KABUPATEN SUMEDANG - Nugrahana Fitria Ruhyana (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2018)
The early age is a substantial period in human development. The long-term benefit from participating in the early childhood education programs is increasing opportunities for the children to complete their higher education in order to get the better welfare future. In Sumedang regency - the location of this study - the childrenâ€™s participations in joining the early childhood education programs had not been optimized yet. Approximately 47% of the children aged 4-6 years had not participated in the early childhood education programs yet. Thus, it was significant to seek out the factors influencing the childrenâ€™s accessibilities to participate in the early childhood education programs in Sumedang regency in order to find out the alternative policy to increase their accessibilities to participate in the early childhoodeducation programs. The research was conducted in 2017 using the quantitative method. The data were obtained from the â€œ2015 Susenasâ€ which involved 300 respondents. The data analysis was performed by using the logistic regression with the 12th version of STATA software. The findings showed that the childrenâ€™s accessibilities to participate in the early childhood education programs in Sumedang regency was determined by the educational background of the head of family, the marital status of the parents, the head of the familyâ€™s income, the number of the family members, and the childrenâ€™s domicile. Giving knowledge about the importance of early childhood education to the lower educational background parents and enlarging the early childhood schoolsâ€™ facilities and infrastructures especially in rural areas of Sumedang regency still needed to be improved in order to have better human resources in the future. References Abdulhak, I. (2003). Memposisikan pendidikan anak usia dini dalam sistem pendidikan nasional. Buletin PADU Jurnal Ilmiah Anak Dini Usia. Jakarta: Dir. PAUD, Dirjend. PLSP, Depdiknas. Apriana, R. (2009). Hubungan Pendidikan Anak Usia Dini (PAUD) dengan perkembangan kognitif anak usia prasekolah di Kelurahan Tinmojoyo Kecamatan Banyumanik Semarang. Skripsi. Semarang: Universitas Diponegoro. Aristin, N. F. (2015). Faktor-faktor yang berpengaruh terhadap anak putus sekolah tingkat Sekolah Menengah Pertama (SMP) di Kecamatan Bondowoso. Jurnal Pendidikan Geografi, 20(1). 30-36. doi: http://dx.doi.org/10.17977/pg.v20i1.5009 Bappeda Kab. Sumedang. (2015). Profil daerah Kabupaten Sumedang. Diakses melalui http://www.sumedangkab.go.id/ Berlinski, S. G., Galiani, S., & Gertler, P. (2006). The effect of pre-primary education on primary school performance. Diakses melalui http://eprints.ucl.ac.uk/15418/ Black, M. M., Walker, S. P., Fernald, L. C. H., Andersen, C. T., DiGirolamo, A. M., Lu, C., â€¦ Grantham-McGregor, S. (2017). Early childhood development coming of age: science through the life course. The Lancet, 389(10064), 77â€“90. doi: https://doi.org/10.1016/S0140-6736(16)31389-7 BPS. (2016a). Statistik daerah Kabupaten Sumedang 2016. Kabupaten Sumedang: Badan Pusat Statistik Kabupaten Sumedang. BPS. (2016b). Survey sosial ekonomi nasional. Diakses melalui https://microdata.bps.go.id/mikrodata/index.php/catalog/769 Chen, Y., & Feng, S. (2013). Access to public schools and the education of migrant children in China. ChinaEconomic Review, 26(1), 75â€“88. doi: https://doi.org/10.1016/j.chieco.2013.04.007 Dewi, N. A. K., Zukhri, A., & Dunia, I. K. (2014). Analisis faktor-faktor penyebab anak putus sekolah usia pendidikan dasar di Kecamatan Gerokgak tahun 2012/2013. Jurnal Jurusan Pendidikan Ekonomi, 4(1), 1-12. http://ejournal.undiksha.ac.id/index.php/JJPE/article/view/1898 Engle, P. L., Fernald, L. C. H., Alderman, H., Behrman, J., Oâ€™Gara, C., Yousafzai, A., â€¦ Iltus, S. (2011). Strategies for reducing inequalities and improving developmental outcomes for young children in low-income and middle-income countries. The Lancet, 378(9799), 1339â€“1353. doi: https://doi.org/10.1016/S0140-6736(11)60889-1 Fahmi, M., & Jewelery, P. G. N. (2015). The effect of pre-school education on academic achievement in Indonesia. Working Paper in Economics and Developments Studies, 201505, 1-18. http://ceds.feb.unpad.ac.id/wopeds/201505.pdf Finnie, R., & Mueller, R. E. (2008). The effects of family income, parental education and other background factors on access to postsecondary education in Canada: Evidence from the YITS. SSRN Electronic Journal, 1â€“52. doi: https://doi.org/10.2139/ssrn.2256114 Heckman, J. (2014). Early childhood development is a smart investment. Diakses melalui https://heckmanequation.org/assets/2014/04/The20Heckman20Curve_v2.jpg Kemdikbud. (2017). Data pokok pendidikan. Diakses melalui http://dapo.dikdasmen.kemdikbud.go.id/ Lake, A. (2011). Early childhood development - Global action is overdue. The Lancet, 378(9799), 1277â€“1278. doi: https://doi.org/10.1016/S0140-6736(11)61450-5 Majzub, R. M., & Rashid, A. A. (2012). School readiness among preschool children. Procedia - Social and Behavioral Sciences, 46, 3524â€“3529. doi: https://doi.org/10.1016/j.sbspro.2012.06.098 Mike, I. O., Nakajjo, A., & Isoke, D. (2008). Socioeconomic determinants of primary school dropout : The logistic model analysis. MPRA Paper, 7851, 1-25. https://mpra.ub.unimuenchen.de/7851/ Musyarofah. (2014). Urgensi pendidikan anak usia dini dalam membangun generasi bangsa yang berkarakter. Al-Fitrah, 9(1), 1-20. http://ejournal.iain-jember.ac.id/index.php/alfitrah/article/view/274 Patmonodewo, S. (2003). Pendidikan anak prasekolah (second). Jakarta: PT. Rineka Cipta. Perdana, N. S. (2015). Faktor-faktor yang berpengaruh terhadap aksesibilitas memperoleh pendidikan untuk anak-anak di Indonesia. Jurnal Pendidikan dan Kebudayaan, 21(3), 279â€“298. doi: http://dx.doi.org/10.24832%2Fjpnk.v21i3.191 Rahman, H. S. (2005). Pendidikan anak usia dini. Yogyakarta: Galah. Rao, N., Sun, J., Chen, E., & Ip, P. (2017). Effectiveness of early childhood interventions in promoting cognitive development in developing countries: A systematic review and meta-analysis. Hong Kong Journal of Paediatrics, 22, 14â€“25. http://www.hkjpaed.org/pdf/2017;22;14-25.pdf Syahra, R. (2003). Modal sosial : Konsep dan aplikasi perkembangan konsep modal sosial. Jurnal Masyarakat dan Budaya, 5(1), 1â€“22. doi: http://dx.doi.org/10.14203/jmb.v5i1.256 Todaro, M. P., & Smith, S. C. (2011). Pembangunan ekonomi di dunia ketiga (11th ed.). Jakarta: Erlangga. UNDP. (2015). Work for human development. Diakses melalui http://hdr.undp.org/en/content/human-development-report-2015-work-human-development Warsilah, H. (2017). Pembangunan inklusif dan kebijakan sosial di Kota Solo Jawa Tengah (Edisi Pert). Jakarta: Yayasan Pustaka Obor Indonesia. Yoshikawa, H., Weiland, C., Brooks-gunn, J., Burchinal, M. R., Espinosa, L. M., Gormley, W. T., â€¦ Zaslow, M. J. (2013). Investing in our future : The evidence base on preschool education. Society for Research in Child Development, (October), 1â€“24. https://www.fcd-us.org/assets/2013/10/20Base20on20Preschool20Education20FINAL.pdf Yusuf, A. A. (2017). Menyelesaikan darurat nutrisi anak sebagai prasyarat pertumbuhan inklusif. Diakses melalui http://sdgcenter.unpad.ac.id/menyelesaikan-darurat-nutrisi-anak-sebagaiprasyarat-pertumbuhan-inklusif/ pada tanggal 1 Maret 2018.